(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The research aimed to investigate the social and educational role of school sports in intermediate schools. The researcher employed a descriptive research methodology using a survey approach to align with the nature of the research problem. The research sample consisted of a group of physical education teachers in schools in Diwaniyah, totaling 60 teachers from various intermediate and high schools. These schools were randomly selected from a total of 347 schools in the district, representing 17.3% of the total schools. Care was taken to select schools from different areas that encompassed a wide geographical region in Diwaniyah, representing various social levels.The researcher designed a questionnaire for physical education teachers in intermediate schools based on personal interviews, sources, and references to formulate the questionnaire items. The response format in the questionnaire consisted of three levels: "always," "sometimes," and "never," corresponding to numerical values of 1, 2, and 3, respectively. The questionnaire included 35 items, and after conducting statistical analysis, 27 items remained.The researcher arrived at several conclusions, including: 1. The presence of significantly positive attitudes among teachers towards the role of school sports.2. Teachers’ responses regarding the social aspect were significantly positive, primarily at the "always" level.As for the recommendations, one of the main ones was the necessity to work on providing effective means and the necessary resources to ensure the success of school sports in intermediate schools due to its importance in students’ physical, social, and educational development.